Direct Ophthalmoscopy Toward the Retinal Periphery: A Quantitative Study - Williams, T David; DiPasquale, A (Canadian Journal of Optometry, 1981)
Examination of the vortex vein region (some 3 mm posterior to the equator of the eye) requires from 3 to 5 D of extra plus power in the direct ophthalmoscope, relative to the power required to examine the optic nerve head. The method used to obtain the above estimate for a single subject is described in an earlier report by Williams and Bader. The purpose of this report is to describe a larger, quantitative, study involving 13 subjects.